Critical pedagogy and Marx, Vygotsky, and Freire : phenomenal forms and educational action research - Villacanas de Castro, Luis Sebastian, 1982- (New York : Palgrave Macmillan, 2015)
'Hidden in the depths of Marx's epistemology is his theory of the phenomenal forms, whose implications have not been sufficiently explored from an educational perspective. This book argues that phenomenal forms pose a major pedagogical obstacle to any endeavour that seeks to expand an individual's awareness of the larger social whole. After situating phenomenal forms in Marx's original framework, the book traces their silent impact on some of the most relevant landmarks and debates of contemporary pedagogical thought, including their misapprehension by Vygotsky and role in Freire's social democracy project as well as the exponential growth recently undergone by participatory forms of educational action research and the difficult dialogue maintained by liberal and critical traditions of pedagogy. This book brings these issues together and assesses their potential to provide a consistent solution to the educational obstacle posed by the phenomenal forms'--
Machine generated contents note: -- Introduction: The Pedagogical Obstacle of the Phenomenal FormsPART I: MARX, FREUD, PEDAGOGY1. Beyond The Ignorant Schoolmaster. On Education, Marxism, and PsychoanalysisPART II: EPISTEMOLOGY, CRITICAL PEDAGOGY, AND LIBERAL PRINCIPLES2. The Pedagogical Problem: Vygotsky's Encounter with Marx's Phenomenal Forms3. The Pedagogical Solution: Freire's Critical Pedagogy and Social DemocracyPART III: THEORY AND PRACTICE OF EDUCATIONAL ACTION RESEARCH4. The Critical Potential of John Elliott's Liberal Pedagogy5. A Practical Case of Participatory Meta-Action Research.
Includes bibliographical references.
Keywords: Marx, Karl, -- 1818-1883 -- Influence; Vygotskii, L. S. -- 1896-1934 -- Influence; Freire, Paulo, -- 1921-1997 -- Influence; Critical pedagogy